Essays on market efficiency and asset pricing : beta risk, fundamental analysis and linkages. - Lee, Chee Tong. (2010)
This thesis examines three distinct but related issues on market efficiency and asset pricing in three separate essays. The first essay looks at the assertion that the standard CAPM is no longer valid. Using data from the Singapore and Malaysian stock markets for the period July 1988 to June 1997, the study finds a fiat relationship between beta and stock returns. But when the sample is split into periods with positive and negative market excess returns, significant relationships are documented. During months with positive market excess returns, a positive relationship between beta and stock returns is found. Conversely, during months with negative market excess returns, a negative relationship between beta and stock returns is established. Hence, findings from this study show that there is a systematic but conditional relationship between beta and stock returns. Surprisingly, no positive risk-return trade-off is documented.